Предмет: Алгебра,
автор: liza35
Упростить выражение
1)sin(пи+альфа)+cos(3 пи/2-альфа)
2)tg(пи/2+альфа)-ctg(2пи-альфа)
3)cos 2альфа+sin^2(пи-альфа)
4)sin альфа // 1+cos альфа +sin альфа // 1-cos альфа
Ответы
Автор ответа:
0
1.-sina-sina=-2*sina
2.-ctga+ctga=0
3.cos2a+(sina)^2=(cosa)^2
4.(sina-sina*cosa+sina+sina*cosa)/(1-cosa)(1+cosa)=
2*sina/(sina)^2=2/sina
Похожие вопросы
Предмет: Биология,
автор: darina948
Предмет: География,
автор: tarakanovvady
Предмет: Английский язык,
автор: Ryazancev160379
Предмет: Математика,
автор: Ayanka
Предмет: Математика,
автор: Кристина13121998